An Optimized Utilization of Battery Backup in MANET Using Modified Firefly Algorithm - et. al., Manoj Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Temporary connection failures and route changes happen in a Mobile Ad Hoc Network (MANET). MANET enjoys extensive variety of applications like in tactical networks, Sensor networks. Much battery backup is required while tuning a node that is far from the sender node While compared to the node which is near in respect to sender, In this paper we are proposing an approach of optimized utilization of battery backup in MANET Battery Backup is a main constraint in mobile ad hoc networks Most of the battery is wasted in tuning to the networks repeatedly there by making the mobile node vulnerable to Jail. This paper emphasize on proper utilization of battery backup by varying the signal strength according the distance of the nodes. Modified FireFly Algorithm (MFFA) is greatly utilized in this research for boosting up of battery backup. The cluster head should maintain a table for battery backup and decision of task distribution will be based on this table.